‘Inanimate Objects’: Human consequences of Australia’s commodified approach to migrant workers during COVID-19 - Berg, Laurie; Farbenblum, Bassina (Anti-Trafficking Review, 2023)
The Australian government has long treated migrant labour as a commodity, a ‘tap’ to be turned on and off in accordance with government or employer perceptions of the labour market. This article examines the Australian government’s policies concerning migrant workers during COVID-19, against the backdrop of its failure to take any meaningful steps to address systemic migrant exploitation over the past decade. It then considers the devastating human consequences of these policies during the first pandemic lockdowns, based on empirical data from over 6,100 temporary migrants collected in mid-2020. The data demonstrate migrant workers’ inability to pay for essential needs (including food and medical care); their lack of access to secure or emergency housing as well as emergency support in the form of cash or food; and their experiences of racism, discrimination, and social exclusion during the pandemic. We conclude that Australia’s commodified approach to migrant workers and acquiescence to exploitation reflected a deeper disavowal of migrants’ humanity and rights. This lens explains the apparent contradiction in which the government first denied or disregarded its legal and moral responsibilities towards them during the immediate crisis posed by the pandemic, while at the same time courting their labour in the context of skills shortages during and after the pandemic.